TAPESTRI DENGAN OBJEK IKAN KOI - YULI MARDINA, Drs. Erwin A, M.Sn., Dra. Ernis, M.Pd. (Serupa The Journal of Art Education, 2019)
This final work aims to realize the form of koi fish in tapestry works. This tapestry work uses the soumak technique, giordes, and is combined with patchwork material on the koi fin. The method of creating this final work uses five stages, namely the stages of preparation, elaboration, synthesis, realization of concepts, and completion.The results were achieved by 7 tapestry works with the titles: Loyalty, Complementary, Togetherness, Courage, Softness, Tranquility, and Joy. It is hoped that the final work will be useful for students majoring in fine arts, able to generate enthusiasm in work, as well as appreciation and comparative work to create better tapestry works in the future.Key words : Koi fish, tapestry